Resonance Energy Transfer to Track the Motion of Lanthanide Ions—What Drives the Intermixing in Core-Shell Upconverting Nanoparticles? - Philipp U. Bastian; Nathalie Robel; Peter Schmidt; Tim Schrumpf; Christina Günter; Vladimir Roddatis; Michael U. Kumke (Biosensors, 2021)
The imagination of clearly separated core-shell structures is already outdated by the fact, that the nanoparticle core-shell structures remain in terms of efficiency behind their respective bulk material due to intermixing between core and shell dopant ions. In order to optimize the photoluminescence of core-shell UCNP the intermixing should be as small as possible and therefore, key parameters of this process need to be identified. In the present work the Ln(III) ion migration in the host lattices NaYF4 and NaGdF4 was monitored. These investigations have been performed by laser spectroscopy with help of lanthanide resonance energy transfer (LRET) between Eu(III) as donor and Pr(III) or Nd(III) as acceptor. The LRET is evaluated based on the Förster theory. The findings corroborate the literature and point out the migration of ions in the host lattices. Based on the introduced LRET model, the acceptor concentration in the surrounding of one donor depends clearly on the design of the applied core-shell-shell nanoparticles. In general, thinner intermediate insulating shells lead to higher acceptor concentration, stronger quenching of the Eu(III) donor and subsequently stronger sensitization of the Pr(III) or the Nd(III) acceptors. The choice of the host lattice as well as of the synthesis temperature are parameters to be considered for the intermixing process.